Teaching history for the common good - Barton, Keith C; Levstik, Linda S (Erlbaum, 2004)
This book reviews research on elementary & middle schools students' historical thinking.Grounded in the theoretical context of mediated action,it addresses the breadth of social practices, settings, purposes & tools that influence students.